2021
DOI: 10.3102/0002831221999782
|View full text |Cite
|
Sign up to set email alerts
|

Off the Beaten Path: Can Statewide Articulation Support Students Transferring in Nonlinear Directions?

Abstract: Students who transfer between colleges risk losing credits and decreasing their chances of degree completion. Despite emerging evidence regarding the effectiveness of articulation agreements to address this challenge, it is unclear if these policies support nonlinear transfer pathways—including lateral transfer between 4-year colleges or reverse transfer to 2-year colleges. I use propensity score weighting to examine a statewide articulation agreement in Ohio that established universal credit acceptance for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…These institutions are stratified by the types of degrees they are able to award as well as through their selectivity (community colleges have open admissions, four year schools do not) and economic opportunities (bachelors degrees often lead to higher paying jobs and are a prerequisite into high paying professional degree programs). Recent research has found that educational outcomes (i.e., graduation rates after transferring) are stratified by the direction of the transfer [ 9 ]. The “direction” refers to the academic pathway of the applicant: “lateral” for students transferring from a four year institution to another four year institution; “vertical” for students transferring from community college to a four year university; and “reverse” for students transferring from four year institutions to community college (the aforementioned study compared lateral and reverse transfers).…”
Section: Introductionmentioning
confidence: 99%
“…These institutions are stratified by the types of degrees they are able to award as well as through their selectivity (community colleges have open admissions, four year schools do not) and economic opportunities (bachelors degrees often lead to higher paying jobs and are a prerequisite into high paying professional degree programs). Recent research has found that educational outcomes (i.e., graduation rates after transferring) are stratified by the direction of the transfer [ 9 ]. The “direction” refers to the academic pathway of the applicant: “lateral” for students transferring from a four year institution to another four year institution; “vertical” for students transferring from community college to a four year university; and “reverse” for students transferring from four year institutions to community college (the aforementioned study compared lateral and reverse transfers).…”
Section: Introductionmentioning
confidence: 99%
“…Students from high-SES backgrounds may similarly use the option of transferring as an adaptive strategy to overcome their initial exclusion to selective colleges and universities. Indeed, research regarding nonlinear transfer behavior reveals two consistent trends: while high-SES students are least likely to leave their first institution at all, among those who do so, a higher proportion transfer laterally to another four-year college whereas the least advantaged students are more likely to transfer to community colleges (Crisp et al, 2021 ; Goldrick-Rab, 2006 ; Goldrick-Rab & Pfeffer, 2009 ; Spencer, 2021 ). In a logistic regression analysis using data from the National Education Longitudinal Study (NELS:88), Goldrick-Rab and Pfeffer ( 2009 ) found that lateral transfers are more likely to come from advantaged socioeconomic backgrounds, net of other factors.…”
Section: Theory and Prior Literaturementioning
confidence: 99%
“…Of the 30 topics generated by the 2015-2016 model, 19 were strongly associated with either lateral (9) or vertical (10) applicants based on results from Welch's t-test (to account for data imbalance). Vertical applicants wrote more about helping others, interpersonal relationships (specifically family and friends), and popular majors (eg.…”
Section: Study One: Variation In Essay Content and Stylementioning
confidence: 99%
“…Recent research has found that educational outcomes (ie. graduation rates after transferring) are stratified by the direction of the transfer [9]. The "direction" refers to the academic pathway of the applicant: "lateral" for students transferring from a four year institution to another four year institution; "vertical" for students transferring from community college to a four year university; and "reverse" for students transferring from four year institutions to community college (the aforementioned study compared lateral and reverse transfers).…”
Section: Introductionmentioning
confidence: 99%